Jewish choices, Jewish voices. - Dorff, Elliot N.; Newman, Louis E., 1956- (Jewish choices, Jewish voices, 2010)
In the newest addition to the Jewish Choices, Jewish Voices series, co-editors Elliot Dorff and Danya Ruttenberg have brought together a diverse group of Jews to comment on how Judaism affects their views and actions regarding sex. Contributors range from adult movie actor Ron Jeremy, to renowned feminist scholar Martha Ackelsberg, to noted writer and blogger Esther Kustanowitz, as well as rabbis, doctors, social workers, and activists. They discuss issues of monogamy, honesty, and communication in dating and marriage; testing for and disclosure of STDs; abortion, sex education, sex work, and sexuality.